Socialization and Digital Marketing Assistance for MSME Community in Jabodetabek Affected by Covid-19 - Ayu Agustin, Cindy (Bina Nusantara University, 2022)
This community service aims to provide socialization and assistance in helping the MSME during the Covid-19 pandemic, where sales and income have decreased. Then digital marketing training assistance was held for the MSME community in Jabodetabek through the Zoom Meeting application to make it easier for them to attend the event. The community was very enthusiastic when participating in the activities of the service implementation team, and when asked for input on mentoring training, there were 18 participants who already understood Digital Marketing; 16 participants understood the use of Digital Marketing; 18 participants were interested in creating Material Content; 20 participants understood the Presentation Material; as many as 20 participants received additional knowledge during the discussion; 20 participants wish to take part in Individual Training; and finally, 20 participants benefited from the socialization and mentoring program.